Smart OEE-SIGMA model for production process optimization - Kareem, Buliaminu; Alabi, Adefowope; Ogedengbe, T. I.; Akinnuli, B. O.; Aderoba, A. A. (Journal of Production Engineering, 2019)
The quest for effective utilization of both humans and machinery is on the increase in order to survive competition. Overall Equipment Effectiveness (OEE) metric application in industry has been facing a challenge of continuing advancement in industrial operations. A smart OEE is required for a quick response to the dynamism in industrial system. In this study, OEE metric is made smart by integrating sigma continuous improvement tool into it for the enhancement of dynamism required of the traditional OEE model measured basically on three factors-availability, performance and quality. System productivity dynamism is measured and predicted through sigma statistical variation of the production process defined as a ratio of delivered output (supply) to the expected (planned) output. The model was applied to a production process of fast moving product. The results obtained for the seven consecutive years (2006 to 2013) for traditional OEE are 100%, 92%, 84%, 86%, 89%, 81%, and 84%, respectively. In the new OEE-Sigma method, productivity can be continuously improved over the years by at most 77%. This indicated that smart OEE-sigma model is a better tool for enhancing continuous improvement in a dynamical processing environment.